Preparation method and application of tear-resistant PVC composite material
By combining aminized nano -nano -nanotoxic oxide and overdue polyester, and mixing with PVC, zinc, and paraffin, tear -resistant PVC composite materials are prepared to solve the problem of poor tear resistance of PVC materials , Significantly improved its mechanical performance.
Patent Information
- Application Number
- CN202410952149.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-16
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-07-16
AI Technical Summary
The poor tear resistance of existing PVC materials limits their application range in manufacturing.
By combining aminized nano -nanotoxicide with overhead polyester, and mixing with PVC, zinc, and paraffin, the tear -to -tear PVC composite material is prepared by plastic and compressive treatment.
It has significantly improved the tear resistance, stretching performance and impact performance of PVC materials, making it suitable for a wider range of application areas.
Smart Images

Figure CN118909359B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of PVC, and in particular to a preparation method and application of a tear-resistant PVC composite material. Background Art
[0002] Polyvinyl chloride, referred to as PVC, is a homopolymer of vinyl chloride. As one of the world's five major general-purpose synthetic resins, it has excellent flame retardancy, mechanical properties, electrical properties, etc. It is widely used in shoes, Japanese plastics, pipes, leather, films and various decorative materials, and has become an indispensable part of human life. However, with the continuous development of science and technology, the existing PVC materials have limited their application scope in the manufacturing industry due to their low strength and poor tear resistance. Therefore, how to improve the tear resistance of PVC materials to enhance their application areas has become a hot topic in current research.
[0003] Nano-silicon dioxide, commonly known as white carbon black, has excellent UV resistance and anti-aging properties, and is widely used in catalysis, medicine, new materials and other fields. Hyperbranched polyester is a substance with ester groups as branched repeating units. Because it has a three-dimensional network molecular chain structure and a large number of terminal reactive functional groups, it can be used in catalysts, nanomaterials, drug carriers and other fields after modification and functionalization.
[0004] For example, the patent with authorization announcement number CN101475672B discloses a method for modifying polyvinyl chloride by in-situ polymerization of nano-silicon dioxide. The invention uses reactive nano-silicon dioxide emulsion and vinyl chloride as raw materials for in-situ polymerization. The impact strength and heat resistance of the prepared nano-silicon dioxide modified polyvinyl chloride material are greatly improved. Summary of the invention
[0005] 1. Technical issues to be resolved
[0006] In view of the deficiencies in the prior art, the present invention provides a preparation method and application of a tear-resistant PVC composite material, and the prepared PVC material has good mechanical properties.
[0007] (II) Technical solution
[0008] A method for preparing a tear-resistant PVC composite material, the preparation method is as follows:
[0009] (1) Add cyanuric chloride to tetrahydrofuran solvent, control the temperature to 0-5°C, add ethanolamine and potassium carbonate, stir and disperse, react for 3-6 hours, filter after the reaction, wash with deionized water, and dry to obtain intermediate 1.
[0010] (2) Add intermediate 1 to deionized water at 0-5°C, stir and disperse, then add acrylic acid thereto, stir and disperse, raise the temperature to 50-70°C, react for 24-48 hours, and after the reaction is completed, rotary evaporate, extract with dichloromethane, wash with deionized water, and dry to obtain intermediate 2.
[0011] (3) Adding amino-modified nano-silica to xylene solvent, stirring and dispersing, and then adding intermediate 2 and p-toluenesulfonic acid, stirring and dispersing, heating to 100-120° C., reacting for 6-12 hours, and after the reaction is completed, filtering, washing with anhydrous ethanol, and drying to obtain intermediate 3.
[0012] (4) Dispersing trimellitic anhydride in tetrahydrofuran solvent, adding intermediate 3 thereto, stirring at 0-5°C for 1-3h, heating to 20-35°C, reacting for 8-14h, then adding methanol and tetraisopropyl titanate thereto, heating to 55-65°C, reacting for 10-20h, and after the reaction, rotary evaporation to obtain nano-silica modified hyperbranched polyester.
[0013] (5) PVC, nano-silica-modified hyperbranched polyester, zinc stearate, and paraffin are added to a mixer and stirred for 2-8 minutes. The mixture is then placed in a double-roll mill at a roller temperature of 160° C. for plastication for 5-15 minutes. The plasticated mixture is placed on a flat vulcanizer while hot for sheeting. A universal sample making machine is used to prepare a sample to obtain a tear-resistant PVC composite material.
[0014] Preferably, in step (1), the mass ratio of cyanuric chloride, ethanolamine and potassium carbonate is 1:0.9-1.5:1.5-2.
[0015] Preferably, in step (2), the mass ratio of the intermediate 1 to acrylic acid is 1:1-1.5.
[0016] Preferably, in step (3), the mass ratio of amino-modified nano-silica, intermediate 2, and p-toluenesulfonic acid is 6-10 g: 1 g: 0.002-0.01 g.
[0017] Preferably, in step (4), the mass ratio of trimellitic anhydride, intermediate 3, methanol and tetraisopropyl titanate is 0.15-0.3:1:0.05-0.1:0.0005-0.002.
[0018] Preferably, in step (5), the molding conditions are 180° C., 15 MPa, and 2 min.
[0019] Preferably, in step (5), the mass ratio of PVC, nano-silicon dioxide modified hyperbranched polyester, zinc stearate, and paraffin is 100:2-10:2-5:0.4-1
[0020] Preferably, the tear-resistant PVC composite material can be used in the fields of footwear, wires and cables, hoses, seals, etc.
[0021] (III) Beneficial technical effects
[0022] The invention uses cyanuric chloride, ethanolamine, acrylic acid, amino nano-silicon dioxide, trimellitic anhydride and the like as raw materials, and synthesizes nano-silicon dioxide modified hyperbranched polyester through substitution reaction, addition reaction and amidation reaction in one step. Finally, the nano-silicon dioxide modified hyperbranched polyester, zinc stearate and paraffin are added to PVC, mixed evenly, plasticized for 5, sheeted and sampled to obtain a tear-resistant PVC composite material.
[0023] The nano silicon dioxide used in the present invention is an inorganic compound and has poor compatibility with organic matter. The present invention organicizes it, reduces the degree of agglomeration, and increases its compatibility with organic matter. When subjected to external force, the nano silicon dioxide acts as a stress concentration point and can absorb more energy, thereby improving the mechanical properties of the PVC material.
[0024] The nano-silicon dioxide modified hyperbranched polyester prepared by a series of reactions and PVC are both polar polymers, and the two have good compatibility. The nano-silicon dioxide modified hyperbranched polyester prepared by the present invention contains a large number of carbonyl groups, which can form intermolecular hydrogen bonds with the methine hydrogen in PVC. Its three-dimensional structure plays a role similar to physical cross-linking, hindering the movement between molecular chains. When subjected to external stress, the stress is dispersed to other molecular chains through the cross-linking points, thereby consuming energy and further improving the mechanical properties of the PVC material. The PVC material prepared by the present invention has been tested and confirmed to have good tear resistance, tensile properties, and impact properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the preparation route of intermediate 3. DETAILED DESCRIPTION
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the specific implementation methods of the present invention will be described below with reference to the accompanying drawings. Obviously, the embodiments described below are only some embodiments of the present invention, and for ordinary technicians in this field, other implementation methods can be obtained based on these embodiments without creative work.
[0027] Preparation method of amino-modified nano-silica: add 10g of nano-silica to 100g of ethanol aqueous solution with a mass ratio of 3:1, ultrasonically disperse for 10min, adjust the pH to 4 with 20% hydrochloric acid aqueous solution, add 40mL of aminopropyltriethoxysilane, heat to 80°C, stir and react for 12h, wash with deionized water after the reaction is completed, and dry to obtain amino-modified nano-silica.
[0028] Example 1
[0029] (1) Add 10 g of cyanuric chloride to tetrahydrofuran solvent, control the temperature to 0° C., add 10 g of ethanolamine and 20 g of potassium carbonate, stir and disperse, react for 4 h, filter after the reaction, wash with deionized water, and dry to obtain intermediate 1.
[0030] (2) At 0°C, 1.2 g of intermediate 1 was added to deionized water, stirred and dispersed, and then 1.2 g of acrylic acid was added thereto, stirred and dispersed, and the temperature was raised to 70°C and reacted for 36 hours. After the reaction was completed, the mixture was rotary evaporated, extracted with dichloromethane, washed with deionized water, and dried to obtain intermediate 2.
[0031] (3) Add 35 g of amino-modified nano-silica to xylene solvent, stir and disperse, then add 4 g of intermediate 2 and 0.04 g of p-toluenesulfonic acid, stir and disperse, heat to 115° C., react for 10 h, and after the reaction is completed, filter, wash with anhydrous ethanol, and dry to obtain intermediate 3.
[0032] (4) 12 g of trimellitic anhydride was dispersed in tetrahydrofuran solvent, 40 g of intermediate 3 was added thereto, the mixture was stirred at 0° C. for 3 h, the temperature was raised to 20° C., and the mixture was reacted for 8 h. Then 4 g of methanol and 0.06 g of tetraisopropyl titanate were added thereto, the temperature was raised to 60° C., and the mixture was reacted for 20 h. After the reaction was completed, the mixture was rotary evaporated to obtain nano-silica modified hyperbranched polyester.
[0033] (5) 100 g of PVC, 2 g of nano-silica-modified hyperbranched polyester, 2 g of zinc stearate, and 0.5 g of paraffin were added to a blender and stirred for 6 min. The mixture was then placed in a double-roll mill at a roller temperature of 160° C. for plasticization for 15 min. The plasticized mixture was placed on a flat vulcanizer for tableting while still hot. The molding conditions were 180° C., 15 MPa, and 2 min. The sample was prepared using a universal sample making machine to obtain a tear-resistant PVC composite material.
[0034] Example 2
[0035] (1) Add 10 g of cyanuric chloride to tetrahydrofuran solvent, control the temperature to 0° C., add 9 g of ethanolamine and 18 g of potassium carbonate, stir and disperse, react for 6 h, filter after the reaction, wash with deionized water, and dry to obtain intermediate 1.
[0036] (2) At 0°C, 1.2 g of intermediate 1 was added to deionized water, stirred and dispersed, and then 1.5 g of acrylic acid was added thereto, stirred and dispersed, and the temperature was raised to 60°C and reacted for 48 hours. After the reaction was completed, the mixture was rotary evaporated, extracted with dichloromethane, washed with deionized water, and dried to obtain intermediate 2.
[0037] (3) Add 30 g of amino-modified nano-silica to xylene solvent, stir and disperse, then add 4 g of intermediate 2 and 0.02 g of p-toluenesulfonic acid, stir and disperse, heat to 110° C., react for 10 h, and after the reaction is completed, filter, wash with anhydrous ethanol, and dry to obtain intermediate 3.
[0038] (4) Disperse 10 g of trimellitic anhydride in tetrahydrofuran solvent, add 40 g of intermediate 3 thereto, stir at 5 ° C. for 1 h, heat to 35 ° C., react for 14 h, then add 2 g of methanol and 0.08 g of tetraisopropyl titanate thereto, heat to 55 ° C., react for 10 h, and after the reaction is completed, rotary evaporate to obtain nano-silica modified hyperbranched polyester.
[0039] (5) 100 g of PVC, 4 g of nano-silica-modified hyperbranched polyester, 4 g of zinc stearate, and 0.4 g of paraffin were added to a blender and stirred for 2 min. The mixture was then placed in a double-roll mill at a roller temperature of 160° C. for plasticization for 15 min. The plasticized mixture was placed on a flat vulcanizer for tableting while still hot. The molding conditions were 180° C., 15 MPa, and 2 min. The sample was prepared using a universal sample making machine to obtain a tear-resistant PVC composite material.
[0040] Example 3
[0041] (1) Add 10 g of cyanuric chloride to tetrahydrofuran solvent, control the temperature to 5° C., add 15 g of ethanolamine and 15 g of potassium carbonate, stir and disperse, react for 3 h, filter after the reaction, wash with deionized water, and dry to obtain intermediate 1.
[0042] (2) At 0°C, 1.2 g of intermediate 1 was added to deionized water, stirred and dispersed, and then 1.5 g of acrylic acid was added thereto, stirred and dispersed, and the temperature was raised to 60°C and reacted for 48 hours. After the reaction was completed, the mixture was rotary evaporated, extracted with dichloromethane, washed with deionized water, and dried to obtain intermediate 2.
[0043] (3) Add 40 g of amino-modified nano-silica to xylene solvent, stir and disperse, then add 4 g of intermediate 2 and 0.01 g of p-toluenesulfonic acid, stir and disperse, heat to 110° C., react for 12 h, and after the reaction is completed, filter, wash with anhydrous ethanol, and dry to obtain intermediate 3.
[0044] (4) 6 g of trimellitic anhydride was dispersed in tetrahydrofuran solvent, 40 g of intermediate 3 was added thereto, the mixture was stirred at 0°C for 2 h, the temperature was raised to 25°C, and the mixture was reacted for 12 h. Then 4 g of methanol and 0.02 g of tetraisopropyl titanate were added thereto, the temperature was raised to 65°C, and the mixture was reacted for 12 h. After the reaction was completed, the mixture was rotary evaporated to obtain nano-silica modified hyperbranched polyester.
[0045] (5) 100 g of PVC, 6 g of nano-silica-modified hyperbranched polyester, 5 g of zinc stearate, and 1 g of paraffin were added to a blender and stirred for 8 min. The mixture was then placed in a double-roll mill at a roller temperature of 160° C. for plasticization for 5 min. The plasticized mixture was placed on a flat vulcanizer for tableting while still hot. The molding conditions were 180° C., 15 MPa, and 2 min. The sample was prepared using a universal sample making machine to obtain a tear-resistant PVC composite material.
[0046] Example 4
[0047] (1) Add 10 g of cyanuric chloride to tetrahydrofuran solvent, control the temperature to 0° C., add 14 g of ethanolamine and 16 g of potassium carbonate, stir and disperse, react for 6 h, filter after the reaction, wash with deionized water, and dry to obtain intermediate 1.
[0048] (2) At 5°C, 1.2 g of intermediate 1 was added to deionized water, stirred and dispersed, and then 1.2 g of acrylic acid was added thereto, stirred and dispersed, and the temperature was raised to 70°C and reacted for 24 hours. After the reaction was completed, the mixture was rotary evaporated, extracted with dichloromethane, washed with deionized water, and dried to obtain intermediate 2.
[0049] (3) Add 24 g of amino-modified nano-silica to xylene solvent, stir and disperse, then add 4 g of intermediate 2 and 0.008 g of p-toluenesulfonic acid, stir and disperse, heat to 100° C., react for 6 h, and after the reaction is completed, filter, wash with anhydrous ethanol, and dry to obtain intermediate 3.
[0050] (4) 8 g of trimellitic anhydride was dispersed in tetrahydrofuran solvent, 40 g of intermediate 3 was added thereto, the mixture was stirred at 0°C for 2 h, the temperature was raised to 25°C, the reaction was carried out for 12 h, 2 g of methanol and 0.05 g of tetraisopropyl titanate were added thereto, the temperature was raised to 60°C, the reaction was carried out for 16 h, and after the reaction was completed, the mixture was rotary evaporated to obtain nano-silica modified hyperbranched polyester.
[0051] (5) 100 g of PVC, 8 g of nano-silica-modified hyperbranched polyester, 3 g of zinc stearate, and 0.8 g of paraffin were added to a blender and stirred for 6 min. The mixture was then placed in a double-roll mill at a roller temperature of 160 ° C for plasticization for 12 min. The plasticized mixture was placed on a flat vulcanizer for tableting while hot. The molding conditions were 180 ° C, 15 MPa, and 2 min. The sample was made using a universal sample making machine to obtain a tear-resistant PVC composite material.
[0052] Example 5
[0053] (1) Add 10 g of cyanuric chloride to tetrahydrofuran solvent, control the temperature to 0° C., add 10 g of ethanolamine and 18 g of potassium carbonate, stir and disperse, react for 5 h, filter after the reaction, wash with deionized water, and dry to obtain intermediate 1.
[0054] (2) At 5°C, 1.2 g of intermediate 1 was added to deionized water, stirred and dispersed, and then 1.8 g of acrylic acid was added thereto, stirred and dispersed, and the temperature was raised to 50°C and reacted for 36 hours. After the reaction was completed, the mixture was rotary evaporated, extracted with dichloromethane, washed with deionized water, and dried to obtain intermediate 2.
[0055] (3) Add 30 g of amino-modified nano-silica to xylene solvent, stir and disperse, then add 4 g of intermediate 2 and 0.04 g of p-toluenesulfonic acid, stir and disperse, heat to 120° C., react for 10 h, and after the reaction is completed, filter, wash with anhydrous ethanol, and dry to obtain intermediate 3.
[0056] (4) 11 g of trimellitic anhydride was dispersed in tetrahydrofuran solvent, 40 g of intermediate 3 was added thereto, the mixture was stirred at 0°C for 2 h, the temperature was raised to 25°C, the reaction was carried out for 10 h, 3 g of methanol and 0.05 g of tetraisopropyl titanate were added thereto, the temperature was raised to 65°C, the reaction was carried out for 14 h, and after the reaction was completed, the mixture was rotary evaporated to obtain nano-silica modified hyperbranched polyester.
[0057] (5) 100 g of PVC, 10 g of nano-silica-modified hyperbranched polyester, 5 g of zinc stearate, and 0.5 g of paraffin were added to a blender and stirred for 4 min. The mixture was then placed in a double-roll mill at a roller temperature of 160 ° C for plasticization for 12 min. The plasticized mixture was placed on a flat vulcanizer for tableting while hot. The molding conditions were 180 ° C, 15 MPa, and 2 min. The sample was made using a universal sample making machine to obtain a tear-resistant PVC composite material.
[0058] Comparative Example 1
[0059] The difference between this comparative example and Example 1 is that in step (5), the nano-silica-modified hyperbranched polyester is not contained.
[0060] With reference to GB / T1040-2006, the tensile strength of the material was tested using a tensile testing machine at a tensile rate of 100 mm / min.
[0061] Refer to GB / T1843-80 and use an impact testing machine to test the impact strength of the material.
[0062] With reference to GB / T529-2008, the tear strength of the material was tested using a tensile testing machine at a tensile rate of 500 mm / min.
[0063] Table 1: Mechanical properties test results of various embodiments and comparative examples
[0064] Tensile strength / MPa <![CDATA[Impact strength / (kJ / m 2 )]]> Tear strength / (N / mm Example 1 49.1 39.6 181.4 Example 2 58.4 42.8 192.6 Example 3 66.2 49.6 207.0 Example 4 64.0 52.3 212.3 Example 5 58.7 51.4 210.7 Comparative Example 1 38.6 32.56 162.8
[0065] As shown in the table, the mechanical property test of embodiment 1-5 is better than comparative example 1, because in embodiment 1-5, nano-silicon dioxide modified hyperbranched polyester is contained, and the nano-silicon dioxide therein is an inorganic compound, and its compatibility with organic matter is poor. The present invention is organicized, reduces the degree of agglomeration, and increases its compatibility with organic matter. When subjected to external force, nano-silicon dioxide, as a stress concentration point, can absorb more energy, thereby improving the mechanical properties of PVC material. The modified hyperbranched polyester and PVC material prepared by a series of reactions of the present invention are both polar polymers, and both have good compatibility, and because the carbonyl contained therein can form intermolecular hydrogen bonds with the methine hydrogen in PVC, a huge cross-linked network structure is formed, which hinders the movement between molecular chains, and when subjected to external stress, the stress is dispersed to other molecular chains through the cross-linking point, thereby consuming energy, and further improving the mechanical properties of PVC material. However, the hyperbranched polyester modified by nano-silicon dioxide is not contained in comparative example 1, so its mechanical properties are poor.
[0066] The above embodiments are only used to illustrate the present invention, but not to limit the present invention. Although the present invention is described in detail with reference to the embodiments, it should be understood by those skilled in the art that various combinations, modifications or equivalent substitutions of the technical solutions of the present invention do not depart from the spirit and scope of the technical solutions of the present invention, and should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a tear-resistant PVC composite material, characterized in that: The preparation method is as follows: (1) Add cyanuric chloride to tetrahydrofuran solvent, control the temperature to 0-5°C, add ethanolamine and potassium carbonate, stir and disperse, react for 3-6 hours, filter after the reaction, wash with deionized water, and dry to obtain intermediate 1; (2) Add intermediate 1 to deionized water at 0-5°C, stir and disperse, then add acrylic acid, stir and disperse, heat to 50-70°C, react for 24-48 hours, and after the reaction is completed, rotary evaporate, extract with dichloromethane, wash with deionized water, and dry to obtain intermediate 2; (3) Adding amino-modified nano-silica to xylene solvent, stirring and dispersing, and then adding intermediate 2 and p-toluenesulfonic acid, stirring and dispersing, heating to 100-120°C, reacting for 6-12 hours, and after the reaction is completed, filtering, washing with anhydrous ethanol, and drying to obtain intermediate 3; (4) dispersing trimellitic anhydride in tetrahydrofuran solvent, adding intermediate 3 thereto, stirring at 0-5°C for 1-3h, heating to 20-35°C, reacting for 8-14h, then adding methanol and tetraisopropyl titanate thereto, heating to 55-65°C, reacting for 10-20h, and after the reaction, rotary evaporation to obtain nano-silica modified hyperbranched polyester; (5) Add PVC, nano-silica modified hyperbranched polyester, zinc stearate and paraffin into a mixer, stir and mix evenly for 2-8 minutes, and then place it in a double-roll mill at a roller temperature of 160°C for plasticization for 5-15 minutes. While hot, place the plasticized mixture on a flat vulcanizer for sheeting, and use a universal sample making machine to make samples to obtain tear-resistant PVC composite materials.
2. The method for preparing the tear-resistant PVC composite material according to claim 1, characterized in that: In the step (1), the mass ratio of cyanuric chloride, ethanolamine and potassium carbonate is 1:0.9-1.5:1.5-2.
3. The method for preparing the tear-resistant PVC composite material according to claim 1, characterized in that: In the step (2), the mass ratio of the intermediate 1 to acrylic acid is 1:1-1.
5.
4. The method for preparing the tear-resistant PVC composite material according to claim 1, characterized in that: In the step (3), the mass ratio of amino-modified nano-silica, intermediate 2, and p-toluenesulfonic acid is 6-10 g: 1 g: 0.002-0.01 g.
5. The method for preparing the tear-resistant PVC composite material according to claim 1, characterized in that: In the step (4), the mass ratio of trimellitic anhydride, intermediate 3, methanol, and tetraisopropyl titanate is 0.15-0.3:1:0.05-0.1:0.0005-0.
002.
6. The method for preparing the tear-resistant PVC composite material according to claim 1, characterized in that: In the step (5), the molding conditions are 180° C., 15 MPa, and 2 min.
7. The method for preparing the tear-resistant PVC composite material according to claim 1, characterized in that: In the step (5), the mass ratio of PVC, nano-silicon dioxide modified hyperbranched polyester, zinc stearate, and paraffin is 100:2-10:2-5:0.4-1 8. An application of the tear-resistant PVC composite material prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The tear-resistant PVC composite material is used in the field of footwear.
Citation Information
Patent Citations
Method for modifying polychloroethylene by in-situ polymerization of nano silicon dioxide
CN101475672B
Polycaprolactone functionalized silicon dioxide toughened epoxy resin floor paint and preparation method thereof
CN112898869A
Elastomer material for shoe sole and preparation method of elastomer material
CN118165209A